(untitled) (Journal of Human Sciences, 2024)
The Arabian Peninsula was witnessing a state of competition between the Adnan tribe, also called the “Qaysiyya tribe," and the Qahtani tribe, called the “Yemeni tribes”. This conflict extended from the pre-Islamic era until after Islam, especially in the Umayyad Caliphate. Because of the hostility that some of these tribes have towards each other, this conflict manifested itself in the form of a struggle over influence, power, and jurisdiction. This conflict left a clear mark on the history of Andalusia. Thus, the general form of rule in Andalusia became the exchange of hegemony over the states in Morocco and Andalusia between the Qaysiyya tribe and the Yemeni tribes. The sons of Umayya, according to their political interests, sometimes approached the Qaysiyya tribe when they shared political interests with them. On the other hand, they approached the Yemeni tribes when they had political benefits with them. They thought these strategies would be the continuation of the Umayya Empire. The Arab-Arab conflicts between the tribes and the civil war between the sons of Umayya, who disputed the caliphate among themselves, were two of the main reasons for the fall of the Umayyad Caliphate in Andalusia.